Optimization of multiplant cogeneration system operation including electric and steam networks - Moslehi, K.; Khadem, M.; Bernal, R.; Hernandez, G. (IEEE transactions on power systems, 1991)
The problem of optimizing the short-term operation of a multiplant cogeneration system in a large industrial complex is solved. A cogeneration system is defined as a system that simultaneously produces electric power (electricity) and thermal power (steam). The cogeneration system model includes both the electric and thermal systems. The electric system model includes generation and transmission. The thermal system model includes the individual plants, which comprise boilers, turbines, condensers, deaerators, pumps, and storage tanks and the interconnecting steam network. The optimization problem has as its objective the minimization of the overall cost of all fuels and make up water used during the scheduling horizon (1 to 24 h), subject to satisfying a number of constraints on electric and steam systems. A novel solution approach is introduced which is based on coordinated optimization of the electric and thermal systems. A production-grade computer program has been developed and tested for a real industrial complex.< >